1986
DOI: 10.1289/ehp.8670239
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and annoyance in the vicinity of coal-fired plants.

Abstract: This study constitutes one part of a program for assessing the impact of coal-fired power plants on the surrounding communities. A questionnaire was mailed to a total of 12,000 subjects living in six areas with coal-fired plants and in matched reference areas. The participation rate was 77.3%. In one coal-fired plant/reference area pair, a more detailed medical examination was carried out among subjects who reported symptoms of the respiratory tract. The match between coal-fired plant and reference areas was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Several studies have emphasized the importance of attitudes to the source of annoyance for reported annoyance (16,17). In the present study, attitudes to air pollution were studied by a series of cumulative items (11). Attitude scores were only slightly related to reported annoyance and could not explain the differences in annoyance between plant areas and their reference areas.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Several studies have emphasized the importance of attitudes to the source of annoyance for reported annoyance (16,17). In the present study, attitudes to air pollution were studied by a series of cumulative items (11). Attitude scores were only slightly related to reported annoyance and could not explain the differences in annoyance between plant areas and their reference areas.…”
Section: Discussionmentioning
confidence: 69%
“…Chi-square tests without Yate's correction were used in the statistical analyses, and two-sided p-values are given. Smoking, education and occupation were controlled in other analyses (11), but the results were essentially the same as those reported below.…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations